The Business Interoperability Decomposition Framework to analyse buyer-supplier dyads - Espadinha-Cruz, Pedro (2019)
The current competitive environment demands cooperative arrangements like buyer-supplier dyads to struggle for the success of supply chains. Managing inter-firm relationships is a decisive and highly demanding activity, whereas business interoperability (BI)is key to achieve meaningful interactions to create value. Nonetheless, cooperation issues due to lack of interoperability constrain the success buyer-supplier dyads. Problems ranging from technical to strategical perspectives of BI may lead to problems like lack of coordination which decrease the supply chain surplus. Interoperability literature provides several contributions and frameworks to deal with different interoperability issues. Nonetheless, it is missing a cohesive framework allowing one to address inter-firm relationships in the full scope of BI. The present paper proposes a framework to support the analysis of interoperability conditions in buyer-supplier dyads. A case study was conducted to demonstrate the framework, and what decisions are required to improve or scale-up cooperation.